PENGARUH PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN PEMBUNGAAN JERUK SATSUMA MANDARIN PADA BEBERAPA KONDISI SUHU - Poerwanto, Roedhy; Inoue, Hiroshi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
Two experiments were conducted at phytotron to investigate the effects of paclobutrazol on vegetative growth and flower bud differentiation of Sat sum a Mandarin (Citrus unshiu Marc.) grown under different temperature conditions. One-year-old Satsuma Mandarin trees budded onto trifoliate orange rootstocks were used in these experiments. The trees were planted in root observation chamber (Experiment I) or Wagner's pot (Experiment II) in late, March of 1988. In experiment I the treatments were temperature (20 & 30oC) and paclobutrazol (treated and not treated). Paclobutrazol was applied 3 times to the soil at the rate of 0.5 gram a.i. per tree per application. The growth of shoots and roots were observed at 5-day intervals. In experiment II the treatments were temperature (15, 20, 25, 30°C and field condition) and paclobutrazol (sprayed to the leaves, drenched to the soil, and none). Paclobutrazol was applied 3 times; foliar application was 1000 ppm and soil application was 0.05 grams a.i. per tree per application. Temperature treatments were done from June to December, 1988. At the end of the treatments, the trees were defoliated and then exposed to 25°C to observe flower bud development. . Paclobutrazol inhibited shoot and root elongation effectively. Paclobutrazol decreased dry weight of the plant top (trunk, stem and leaves), but increased root dry weight. Paclobutrazol also increased the root diameter by increasing the number of-cortex cells, although the cell diameter was not different. Paclobutrazol affected nutrients distribution; it decreased nutrients in the top part of trees, and increased nutrient in the root. Effects of paclobutrazol in flower bud differentiation was not significant.